Implikasi Hukum Pemberlakuan UU HKPD terhadap Pendapatan Asli Daerah (PAD) - Prima Andi Nugroho; Aturkian Laia (INDO PUBLISHING, 2026)
The enactment of Law Number 1 of 2022 on HKPD marks a new chapter in fiscal decentralization to strengthen regional fiscal independence. This article analyzes the central-regional financial arrangements, their legal implications for Local Genuine Revenue (PAD), and the challenges and opportunities of their implementation. Using a normative juridical method, the study shows that the HKPD Law brings structural changes through the simplification of tax types into the Certain Goods and Services Tax (PBJT) and the introduction of tax option instruments. Juridically, this regulation expands yet limits regional taxing powers and mandates the unification of local regulations. Its implementation opens opportunities for PAD optimization through automated option distribution, but object simplification potentially reduces the revenue base and demands institutional and administrative readiness. This article recommends strengthening legal oversight of derivative regulations and restructuring PAD strategies aligned with the HKPD Law.